(untitled) - Klein, Natalie (Cambridge, UK, 2004)
Some say that one of the most significant aspects of the 1982 Convention is that it includes a mechanism for compulsory arbitration or adjudication; others say the feature does not diverge much from those in other treaties. Klein (international law, Macquarie U., Sydney) tests the two views by investigating whether compulsory dispute settlement is requisite for the operation of the Convention, exploring the interaction between its substantive provisions and the procedural devices available to resolve differences in the interpretation and application of those substantive rules. To discern the connection between the substance and the procedure, she analyzes what the drafters of the Convention intended, what was actually produced in the Convention, and what is likely to happen in the future. The study is based on her 2003 Ph.D. dissertation for Yale University.
Keywords: Law of the sea,Arbitration, international